Selective Laser Melting of Diamond-Containing or Postnitrided Materials Intended for Impact-Abrasive Conditions: Experimental and Analytical Study - Ramin Rahmani; Maksim Antonov; Lauri Kollo (Advances in Materials Science and Engineering)
Materials with higher wear resistance are required in various applications including cutting elements (drag bits) of soft ground tunnel boring machines (TBM) to increase the productivity and to reduce the risk for workers involved in exchange operations (dangerous hyperbolic conditions). In recent work, two types of materials were produced by combining 3D printing (selective laser melting, SLM) of cellular lattice structures and spark plasma sintering (SPS) methods. The lattices were printed from (1) 316L stainless steel with diamond and (2) Ti6Al4V with nitriding. The effect of diamond content (5%, 10%, and 20%; nickel-coated particles) and unit cell size on performance was studied. The titanium alloy lattice was nitrided to increase its hardness and wear resistance. The effect of nitriding temperature (750°C, 900°C, and 1050°C) and lattice volume fraction (6%, 15%, and 24%, vol.) was investigated, and the optimized conditions were applied. The lattices were filled with 316L and Ti6Al4V powders, respectively, and consolidated by SPS. Samples were tested with the help of laboratory impact-abrasive tribodevice. Laboratory results have shown that both reinforcing approaches are beneficial and allow improvement of wear resistance in impact-abrasive conditions with great potential for TBM or similar applications. Modelling with the help of finite element method has shown that lattice structure enables reduction of peak local stresses in scratching and impact conditions.